Cover Picture: α‐Cyclodextrin Encapsulation of Bicyclo[1.1.1]pentane Derivatives: A Storable Feedstock for Preparation of [1.1.1]Propellane (Angew. Chem. Int. Ed. 5/2021). Issue 5 (28th December 2020) - Matsunaga, Tadafumi; Kanazawa, Junichiro; Ichikawa, Tomohiro; Harada, Mei; Nishiyama, Yusuke; Duong, Nghia Tuan; Matsumoto, Takashi; Miyamoto, Kazunori; Uchiyama, Masanobu
Abstract : α ‐Cyclodextrin encapsulation of bicyclo[1.1.1]pentane (BCP) derivatives and new protocols for deiodination reactions of 1, 3‐diiodo BCP to afford [1.1.1]propellane are described by Junichiro Kanazawa, Kazunori Miyamoto, Masanobu Uchiyama et al. in their Communication on page 2578 . The combination of these methodologies enables on‐demand preparation of [1.1.1]propellane in various (protic/aprotic/polar/non‐polar) solvents under mild conditions.